Assessment of Kisan Mobile Advisory (KMA) Service For Dissemination Of Agricultural Information - Jagmohan Singh; Parvinder Singh; Raminder Kaur (Journal of Agricultural Extension Management, 2016)
The present study was undertaken on 350 farmers, 100 in-service personnel and 50 input dealers out of the total 3330 users registered with KVK Amritsar. After sending the messages for three years (2012, 2013 and 2014) responses from the selected KMA beneficiaries were obtained during March 2015 through telephone by calling them on their respective mobile numbers. Messages were needful and timely as reported by 80.86 per cent of farmers and 82 and 68 per cent of extension personnel and input dealers respectively. The delivered messages were medium understandable for 47.14 per cent of farmers, highly understandable for 85 per cent of extension personnel and for 66 per cent of the input dealers. The messages were fully applicable as perceived by 7 5. 71 per cent of farmers, while 22 per cent of the farmers perceived as medium applicable and 02 per cent reported as partially applicable. It was also found that 8 7 per cent messages were fully applicable for extension personnel and 74 per cent for input dealers. The overall high impact of KMA services was reported by 80.86 per cent farmers, 87 per cent of extension personnel and 7 4 per cent of input dealers. Low impact of two per cent each was reported by all the respondents viz., farmers, extension personnel and input dealers in Amritsar district of Punjab